Arbitration law in KSA: past, present and future - Sufian, Azlinor (2017)
Kingdom of Saudi Arabia (KSA) is one of the countries in the world that practicing the sharia law. Accordingly all the royal decrees which are enforced in the country are based on sharia, predominant by the teaching of Hanbali School of law. In general all laws in KSA are codified, (with the exception to the family law), including the arbitration law. The arbitration law in KSA has gone through several phases beginning from the law which was introduced in 1350H/1931G. The old law was very conservative in nature as compared to the current law on arbitration which is based on UNCITRAL Model law. This new law was introduced in 1403H/2012G. The objectives of this paper are to present the development of arbitration law in KSA and the extent of its implementation. It also analyzes the functions of governing bodies for arbitration in KSA. Using the qualitative method, this paper evaluate the development of arbitration law in KSA and its future, where it reveals that the provisions in its royal decree are in par with the international practices, nevertheless in practice, it still struggling in implementing the whole law.